Health-related quality of life trajectory of treatment-naive patients with Merkel cell carcinoma receiving avelumab - Bharmal, Murtuza; Nolte, Sandra; Lebbé, Céleste; Mortier, Laurent; Brohl, Andrew S; Fazio, Nicola; Grob, Jean-Jacquez; Pusceddu, Sara; Hanna, Glenn J; Hassel, Jessica C.; Kiecker, Felix; Ellers-Lenz, Barbara; et al. (Future oncology, 2020)
Aim: To evaluate changes in health-related quality of life (HRQoL) in a Phase II trial (NCT02155647) of treatment-naive patients with metastatic Merkel cell carcinoma treated with avelumab (15-month follow-up). Materials & methods: Mixed-effect Models for Repeated Measures were applied to HRQoL data (FACT-M; EQ-5D-5L) to assess changes over time. Clinically derived progression-free survival was compared with HRQoL deterioration-free survival. Results: Overall, we saw relative stability in HRQoL among 116 included patients, with nonprogression associated with statistically and clinically meaningful better HRQoL compared with progressive disease. Deterioration-free survival rates (49-72% at 6 months, 40-58% at 12 months) were consistently higher/better compared with progression-free survival rates (41/31% at 6/12 months). Conclusion: These findings show unique longitudinal HRQoL data for treatment-naive metastatic Merkel cell carcinoma patients treated with avelumab. Clinical trial registration: NCT02155647 (ClinicalTrials.gov). Infographic: A PDF version of this infographic is available as supplemental material.
Gesehen am 25.09.2025